Creating ambient intelligent space in downstream apparel supply chain with radio frequency identification technology from lean services perspective. Issue 2 (19th March 2010) - So, Stuart C.K.; Sun, Hongyi
Radio frequency identification (RFID) technology realises ambient intelligence (AmI) in real life and offers not only user-friendly shopping experience to customers, but also agile and responsive store operations to merchants. Applying lean services in apparel retail operations may equally benefit to this industry. In this research, recent studies on RFID technology adoption were evaluated to help develop research instrument. It followed by a comprehensive case study on the implementation of an RFID-based smart retail system in an apparel retailer. Four adoption factors of this new initiative from both individual and organisational perspectives were identified: 1) compatibility; 2) costs; 3) ease of use; 4) security and trust. A business value-added framework was then proposed for further research based on the adoption factors and lean improvement objectives. Lastly, managerial implications were discussed with the aim to provide insights of better adopting this technology through the alleviation of practical problems and user concerns.